Controlling reactivity in the Fujiwara–Moritani reaction: Examining solvent effects and the addition of 1, 3-dicarbonyl ligands on the oxidative coupling of electron rich arenes and acrylates. Issue 6 (6th February 2020) - Jones, Roderick C.
Graphical abstract: Highlights: The CH arylation of electron rich acrylates is described. Simple and direct method for controlling reactivity in electron rich olefination. Investigation of solvent effect on reaction outcome. New insights of 1, 3-dicarbonyl ligand effects on Fujiwara–Moritani reaction. ESI-MS study used to identify reaction intermediates. Abstract: A palladium-catalysed direct alkenation of electron rich arenes in the presence of K2 S2 O8 with an acetic acid/1, 4-dioxane solvent combination has been developed. The 1, 4-dioxane co-solvent dramatically influences the rate of reaction, giving selectively disubstituted alkenes, while the addition of acetylacetone ligands was shown to increase site selectivity for the alkenation of monofunctionalized arenes. The participation of these carbonyl ligands has been confirmed by ESI-MS studies, with some key in situ intermediates in the catalytic cycle identified. A variety of electron rich arenes and olefinic substrates can be utilised in the direct oxidative coupling to give disubstituted alkenes in moderate to good yields.